2002
DOI: 10.1375/136905202320906200
|View full text |Cite
|
Sign up to set email alerts
|

Sri Lankan Twin Registry

Abstract: Sri Lanka is an island with genetic diversity between the five main population groups. Our twin registry is the first in the developing world. Initially, we established a volunteer cohort of 4600 twin pairs through a competition advertised in the media. In addition, we have volunteer cohorts, birth registration-based cohorts through hospitals, and community-based cohorts. There is also a nationwide population-based younger twin cohort (1992-1997) traced through the Department of Birth and Death Registration. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Researchers have accessed many data sources when establishing twin registers, including birth records (Anderson et al, 2002;Bergem, 2002;Krueger & Johnson, 2002;Skytthe et al, 2002;Sumathipala et al, 2002), notification of multiple pregnancies from health professionals (Derom et al, 2002;Glinianaia et al, 2002), school records (Anderson et al, 2002), military service records (Goldberg et al, 2002;Page, 2002) and national population or health insurance registers (Bergem, 2002;Stazi et al, 2002;Sung et al, 2002;Yang et al, 2002). Most volunteer-based registers rely on advertising to recruit participants, and this is achieved using various media outlets, referrals by health professionals, and contact through twins clubs, parishes, schools and hospitals (Baker et al, 2002;Boomsma et al, 2002b;Hayakawa et al, 2002;Hopper, 2002;Jang et al, 2002;Spector & MacGregor, 2002;Spinath et al, 2002;Strassberg et al, 2002).…”
mentioning
confidence: 99%
“…Researchers have accessed many data sources when establishing twin registers, including birth records (Anderson et al, 2002;Bergem, 2002;Krueger & Johnson, 2002;Skytthe et al, 2002;Sumathipala et al, 2002), notification of multiple pregnancies from health professionals (Derom et al, 2002;Glinianaia et al, 2002), school records (Anderson et al, 2002), military service records (Goldberg et al, 2002;Page, 2002) and national population or health insurance registers (Bergem, 2002;Stazi et al, 2002;Sung et al, 2002;Yang et al, 2002). Most volunteer-based registers rely on advertising to recruit participants, and this is achieved using various media outlets, referrals by health professionals, and contact through twins clubs, parishes, schools and hospitals (Baker et al, 2002;Boomsma et al, 2002b;Hayakawa et al, 2002;Hopper, 2002;Jang et al, 2002;Spector & MacGregor, 2002;Spinath et al, 2002;Strassberg et al, 2002).…”
mentioning
confidence: 99%
“…[12][13][14] Twin birth registries are rare in low and middle income countries(LMIC) and twin specific research is generally based on hospital based studies, secondary analyses of interventional trials or retrospective analyses of demographic and health survey (DHS) data, all with significant limitations and bias. [15][16][17] In LMICs medical record documentation is suboptimal which may affect the data quality. 16 Previous studies have shown increasing maternal age and parity have been found to be strongly associated with increased incidence of twinning.…”
Section: Discussionmentioning
confidence: 99%
“…Twin analysis provides an important method to analyze and study this issue. Current available twin databases are almost exclusively based in western countries, such as the Norwegian Twin Registry (Bergem, 2002), the Danish Twin Registry (Skytthe et al, 2002), the Swedish Twin Registry (Pedersen et al, 2002), the Netherlands Twin Registry (Boomsma et al, 2002), Minnesota (Iacono & McGue, 2002) and Wisconsin (Van Hulle et al, 2002) Twin Twin Registry,Virginia and North Carolina Twin Registries and Mid-Atlantic Twin Registry, Sri Lankan Twin Registry (Sumathipala et al, 2002). Several attempts have also been made in China to establish twin databases; for example, in 2002, Huiying Yang established a database of 8583 pairs of twins (Yang, 2002).…”
Section: Twin Method Twin Databases Sq and Chongqing Children Twins mentioning
confidence: 99%